2021
DOI: 10.1002/eji.202048681
|View full text |Cite
|
Sign up to set email alerts
|

CCL25 and CCR9 is a unique pathway that potentiates pannus formation by remodeling RA macrophages into mature osteoclasts

Abstract: This study elucidates the mechanism of CCL25 and CCR9 in rheumatoid arthritis (RA). RA synovial fluid (SF) expresses elevated levels of CCL25 compared to OA SF and plasma from RA and normal. CCL25 was released into RA SF by fibroblasts (FLS) and macrophages (MΦs) stimulated with IL‐1β and IL‐6. CCR9 is also presented on IL‐1β and IL‐6 activated RA FLS and differentiated MΦs. Conversely, in RA PBMCs neither CCL25 nor CCR9 are impacted by 3‐month longitudinal TNF inhibitor therapy. CCL25 amplifies RA FLS and mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…Pro-inflammatory macrophages also secrete angiogenic factors such as VEGF or TGF-a/b to increase new blood vessel formation (101), as well as influencing fibroblasts to secrete RANKL, leading to bone erosion (99). In this context, macrophages may also be able to directly differentiate into mature osteoclasts given the correct environmental cues such as CCL25/CCR9 to further increase bone erosion (102,103). This concept is supported by the identification of an osteoclastogenic macrophage subset in the synovial tissue of mice with collageninduced arthritis (104).…”
Section: Macrophage Subsets In Rheumatoid Arthritismentioning
confidence: 99%
“…Pro-inflammatory macrophages also secrete angiogenic factors such as VEGF or TGF-a/b to increase new blood vessel formation (101), as well as influencing fibroblasts to secrete RANKL, leading to bone erosion (99). In this context, macrophages may also be able to directly differentiate into mature osteoclasts given the correct environmental cues such as CCL25/CCR9 to further increase bone erosion (102,103). This concept is supported by the identification of an osteoclastogenic macrophage subset in the synovial tissue of mice with collageninduced arthritis (104).…”
Section: Macrophage Subsets In Rheumatoid Arthritismentioning
confidence: 99%
“…In the joint cavity, synovial macrophages from the circulation can be used as osteoclasts precursors, but there is no evidence that resident synovial macrophages can differentiate into osteoclasts (161). Generally speaking, in the joint inflammation environment of RA, circulating monocytes will continue to transfer to the joint cavity and differentiate into osteoclasts to promote joint inflammation (161,162). Evidence showed that the monocytes that can differentiate into osteoclasts are CD14 positive but CD16 negative.…”
Section: The Macrophage-osteoclast Axis In Rheumatoid Arthritismentioning
confidence: 99%
“…Additionally, GSH-Px can relieve inflammation-induced osteolytic bone destruction by breaking down LPS ( Islam et al, 2007 ; Li et al, 2020 ). Upregulating GSH-PX activity can inhibit pro-inflammatory factors associated with osteoclast maturation genes, such as iNOS, IL-1β, and tumor necrosis factor-alpha (TNF-α) ( Kruger et al, 2010 ; He et al, 2020 ; Li et al, 2020 ; Umar et al, 2021 ). GSH-Px may be the key link in the oxidative stress-inflammation reaction in postmenopausal osteoporosis with great potential research value.…”
Section: Antioxidant Enzymesmentioning
confidence: 99%